2019
DOI: 10.1080/21691401.2019.1699820
|View full text |Cite
|
Sign up to set email alerts
|

CYLD expression in dendritic cells involved in the immunoregulation of pulmonary adenocarcinoma via NF-κB pathway

Abstract: View related articlesView Crossmark data Citing articles: 1 View citing articles CYLD expression in dendritic cells involved in the immunoregulation of pulmonary adenocarcinoma via NF-jB pathway

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Our results indicated that CYLD-knockout DCs show decreased signaling and nuclear translocation of NF-kB. Inhibition of the NF-kB pathway inhibits the DCs-induced proliferation and function of CD4 + T cells, indicating that CYLD exerts a positive effect on T-cell function [9] . In this study, DCs were transfected with a miR-124-3p mimic or miR-124-3p inhibitor, and were then co-cultured with CD4 + T cells.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Our results indicated that CYLD-knockout DCs show decreased signaling and nuclear translocation of NF-kB. Inhibition of the NF-kB pathway inhibits the DCs-induced proliferation and function of CD4 + T cells, indicating that CYLD exerts a positive effect on T-cell function [9] . In this study, DCs were transfected with a miR-124-3p mimic or miR-124-3p inhibitor, and were then co-cultured with CD4 + T cells.…”
Section: Discussionmentioning
confidence: 61%
“…Our previous studies on the distribution and differential expression of CYLD and DCs in lung cancer tissues and corresponding adjacent tissues showed that CYLD expression is correlated with the distribution of mDCs in lung cancer and adjacent tissues. Those studies showed that increased expression levels of the CYLD protein in lungcancer tissues are correlated with increased rate of DCs maturation [9] . miRNAs play important roles in regulating gene expression in tumor biology [10] .…”
Section: Discussionmentioning
confidence: 99%
“…DCs play a key role in tumor immunotherapy, and relevant research is ongoing. CYLD is a deubiquitination enzyme that regulates various signaling pathways in physiological processes (9). Our previous studies on the distribution and differential expression of CYLD and DCs in lung cancer tissues and corresponding adjacent tissues showed that CYLD expression is correlated with the distribution of mDCs in lung cancer and adjacent tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies on the distribution and differential expression of CYLD and DCs in lung cancer tissues and corresponding adjacent tissues showed that CYLD expression is correlated with the distribution of mDCs in lung cancer and adjacent tissues. Those studies showed that increased expression levels of the CYLD protein in lung-cancer tissues are correlated with increased rate of DCs maturation (9).…”
Section: Discussionmentioning
confidence: 99%
“…Immune genes of LUAD brain metastasis were involved in the adaptive immune response, B cell differentiation, myeloid leukocyte differentiation, cellular extravasation, positive regulation of leukocyte migration, interleukin-12 production, activation of immune response, regulation of inflammatory response, regulation of cytokine production, leukocyte migration, leukocyte activation involved in immune response, leukocyte differentiation, and other biological functions, and might be involved in the regulation of cellular senescence, c-type lectin receptor signaling pathway, natural killer cell mediated cytotoxicity, CAMs, primary immunodeficiency, and NF-κB signaling pathway, among others. Studies have reported that the adaptive immune response, the NF-κB signaling pathway, and the IL12 signaling mechanism, among others, play important roles in the progression of LUAD (17)(18)(19)(20). For example, IL33 inhibited the growth of LUAD by regulating dendritic cells (DCs).…”
Section: Discussionmentioning
confidence: 99%